2021
DOI: 10.1371/journal.pone.0251234
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological study of SARS-CoV-2 infection in East Java, Indonesia

Abstract: Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to a global pandemic, including Indonesia. However, there are only limited data regarding the precise prevalence of the COVID-19 pandemic in Indonesia. Here, to estimate the magnitude of SARS-CoV-2 infection in East Java, Indonesia, we investigated the prevalence of immunoglobulin G (IgG) antibodies. We enrolled 1,819 individuals from June to December 2020 and observed that the subjects’ overall p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 27 publications
2
24
4
Order By: Relevance
“…These data likely reflect the low incidence of COVID-19 within the country and are in agreement with the few confirmed cases in 2020 and low reported rates of hospitalisation of patients with respiratory illnesses in Lao PDR [7] . Low seroprevalence in the general population in Lao PDR, 2020 is similar to studies from other countries in southeast Asia where COVID-19 cases were low [30] and in contrast to high incidence countries [31] . Healthcare workers are particularly at risk of infection and our data showing low seroprevalence are again in agreement with studies from countries with low reported COVID-19 cases [32][33][34] , and in contrast to higher seroprevalence in countries with higher incidence of confirmed COVID-19 cases, including in East Asia [35] .…”
Section: Discussionsupporting
confidence: 80%
“…These data likely reflect the low incidence of COVID-19 within the country and are in agreement with the few confirmed cases in 2020 and low reported rates of hospitalisation of patients with respiratory illnesses in Lao PDR [7] . Low seroprevalence in the general population in Lao PDR, 2020 is similar to studies from other countries in southeast Asia where COVID-19 cases were low [30] and in contrast to high incidence countries [31] . Healthcare workers are particularly at risk of infection and our data showing low seroprevalence are again in agreement with studies from countries with low reported COVID-19 cases [32][33][34] , and in contrast to higher seroprevalence in countries with higher incidence of confirmed COVID-19 cases, including in East Asia [35] .…”
Section: Discussionsupporting
confidence: 80%
“…The Indian government-initiated serum surveys indicate a 24.1% positivity of serum antibody (15). An 11.4% overall prevalence of IgG antibodies is demonstrated, but the prevalence of IgG in laboratory technicians was much higher than in other professions in East Java, Indonesia (12). The Singapore government tested all the migrant workers in dedicated hostels through PCR and serological methods within 4 months and obtained an overall infection rate of 56.1% (16).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the survey ( 11 ) by the Indian Council of Medical Research (ICMR), around 21.4% of 28,589 adolescent participants had been infected as of February 4, 2021. Another serological study ( 12 ) found that the prevalence of IgG antibody (indication of past infection) to SARS-CoV-2 was 11.4% in East Java, Indonesia. A serological study ( 13 ) among healthcare workers in the Kathmandu valley, Nepal, showed a 23% positivity for polymerase chain reaction (PCR) testing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results generally found a higher prevalence of the actual COVID-19 infection than the reported one [ 15 ], such as a study in Guilan, Iran that discovered a 22% seroprevalence, 323 times as high as the reported cases [ 16 ]. To date, only one study explores COVID-19 seroprevalence in Indonesia, particularly in East Java,—a province that frequently contributes largely to the high cumulative COVID-19 cases in the country [ 17 ]. Therefore, it is vital to conduct more seroprevalence studies, especially in the special capital region of Jakarta that constantly records the highest cases of COVID-19 in Indonesia [ 2 ].…”
Section: Introductionmentioning
confidence: 99%